# Yahoo Web Search

1. Sort by

1. ### calculus area between the curves?

...(x_1,x_2)P(x)dx - Int(x_1,x_2)H(x)dx ?= 25 LHS = 25 ==> CHECKED

1 Answers · Science & Mathematics · 23/07/2011

2. ### coolean algebra. so confused!?

Your answer for the first qquestion is correct. For second question follow the two DeMorgan laws: (A+A)' = A'.A' (A.A)' = A'+A'

2 Answers · Science & Mathematics · 19/05/2007

Your first answer is correct -- quite a few steps though you cold say XX'+YY+XY+X'Y ≟ Y 0 + Y + (X + X')Y ≟ Y and since (X + X') =1 0 + Y + Y ≟ Y...

1 Answers · Science & Mathematics · 19/05/2007

4. ### Mathematics Differential equations help please!?

(11-2x)/((x+3)(x+1)) dx = dt. Take a integration!!!

2 Answers · Science & Mathematics · 21/01/2012

5. ### Is there a rule for surge waves in rapidly varied flow, in fluid mechanics.?

Hint: http://nptel.iitm.ac.in/courses/IIT-MADRAS/Hydraulics/pdfs/Unit38/38_1.pdf http://www.scribd.com/doc/6554968/7708DC10620677#fullscreen:on Remember that up-stream and down-stream velocity are different.

1 Answers · Science & Mathematics · 10/05/2010

6. ### Please solve by induction? I got close but ended up with an unbalanced term =(?

To show it to be true for n = k + 1, you have the left hand side equal to 1^2 + 2^2 + ... + k^2 + (k+1)^2 Subbing your assumption for it being true for n = k gives k(k+1)(2k+1)/6 + (k+1)^2 Then the algebra goes as follows: = [k(k+1)(2k+1)/6] + k² + 2k + 1...

1 Answers · Science & Mathematics · 07/11/2011

7. ### 1/5 ln |y-2|- 1/5 ln |y+3| = x+c .... find y?

(1/5)*ln[abs(y - 2)] - (1/5)*ln[abs(y + 3)] = x + c I couldn't get a solution closed form but I got this: for Y=< -3 or Y => 2 Y = {2 + 3*e^[5*(x + c)]}/{1 - e^[5*(x + c)]} for -3 =< Y =< 2...

1 Answers · Science & Mathematics · 20/11/2012

8. ### Generalized Hooke's Law in Stiffness form derivation?

Hooke's Law for isotropic materials http://www.efunda.com/formulae/solid_mechanics/mat_mechanics/hooke_isotropic.cfm

2 Answers · Science & Mathematics · 07/11/2013

9. ### Derivatives help? (d/dx) etc. for engineering?

TS is a product. Taking the derivative, using the product rule, d(TS) = T*d(S) + S*d(T) if d(TS) = T*d(S) , then S*d(T) must be zero, e.g. T is a constant hth http://www.answers.com/topic/product...

2 Answers · Science & Mathematics · 12/04/2011